Storming the citadel: Engaging adult educators in the critical analysis of adult educational theory - Stephen Brookfield (Adult Education Research Conference, 1995)
Despite numerous injunctions and exhortations by adult educators about the value of doing a critical analysis of professional literature, very few suggestions are available on how this might be done. In this paper I want to build on my own experience structuring a critical reading of theory around four general categories of questions (epistemological, experiential, communicative and political). Asking a series of questions about a text provides a structure for critical inquiry that makes this activity seem less daunting. The reader has a road map to take her into unfamiliar terrain.